Range size heritability patterns in Carnivora arise from the interplay between evolutionary and geographic constraints - Macháč, Antonín (Jihočeská univerzita, 2011)
The thesis explores how the range sizes of carnivorans are shaped by geographic and evolutionary constraints. Employing modern spatial analyses and phylogenetic comparative methods, we illustrate that phylogenetically conserved climate tolerances delimit species? geographic constraints, which in turn shape the species? range size. Range size heritability patterns emerge as a consequence of this interplay between geographic and evolutionary constraints.
Range size heritability patterns in Carnivora arise from the interplay between evolutionary and geographic constraints
Keywords: macroecology; evolution; biogeography; Carnivora; species selection; PVR; macroecology; evolution; biogeography; Carnivora; species selection; PVR